2011
DOI: 10.1007/s00408-011-9352-x
|View full text |Cite
|
Sign up to set email alerts
|

Cough Reflex in Lung Transplant Recipients

Abstract: Lung transplantation has become the standard of care for particular individuals with advanced lung disease. However, this surgical procedure involves interruption of the lower vagal nerve fibers which leads to loss of the protective cough reflex. Injury of the neural pathways involved with the sensory limb of the cough reflex is associated with an increased risk of complications involving the allograft. While loss of the cough reflex was once considered permanent, recent evidence indicates functional and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…The respiratory tract is particularly at risk for infection because denervation of the transplanted lung results in impaired coughing and slowing of mucociliary clearance. 17,18 Our most notable findings concerned the outcomes of these infections. Contrary to prior reports of high mortality rates among solid organ transplant recipients with staphylococcal infections, 15,19 we found that the 30-and 90-day mortality rates were only 7% and 12%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The respiratory tract is particularly at risk for infection because denervation of the transplanted lung results in impaired coughing and slowing of mucociliary clearance. 17,18 Our most notable findings concerned the outcomes of these infections. Contrary to prior reports of high mortality rates among solid organ transplant recipients with staphylococcal infections, 15,19 we found that the 30-and 90-day mortality rates were only 7% and 12%, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…using a mechanosensory stimulus, and described as normal, attenuated or absent. While there were more observations of absent cough reflex in patients with lower levels of consciousness on the Glasgow Coma Scale, there were also patients in which cough reflex was present at the lowest level of consciousness (37). More recently, this study has been replicated in a larger sample of 208 patients admitted with trauma, poisoning, neurological and cardiorespiratory conditions, etc., and level of consciousness ranging from full (Glasgow Coma Scale score 15) to comatose (Glasgow Coma Scale score ≤8) (39).…”
Section: Attenuation Of the Cough Reflex Due To Reduced Level Of Consmentioning
confidence: 77%
“…It is widely recognized that LTR are at particular risk for respiratory tract infections by environmental molds. This susceptibility is a result of the continuous exposure of the transplanted organ to the external environment, the frequent need for prolonged mechanical ventilation , impaired mucociliary clearance , and profound immune suppression . Moreover, patients awaiting lung transplantation are commonly colonized with fungi as a result of their underlying diseases.…”
Section: Discussionmentioning
confidence: 99%